2021
DOI: 10.1111/jcpe.13485
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of a point‐of‐care aMMP‐8 test in the discrimination of periodontal health and disease

Abstract: Aim: To assess the diagnostic utility of an oral rinse active matrix metalloproteinase-8 (aMMP-8) point-of-care test (POCT) for differentiating periodontal health, gingivitis, as well as different stages and grades of periodontitis. Materials & Methods:The aMMP-8 index test was undertaken in 408 consecutive adults, followed by a full-mouth periodontal examination. The reference standard was the 2017 World Workshop classification of periodontal diseases. Sensitivity, specificity, and the area under the receiver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
90
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(104 citation statements)
references
References 56 publications
8
90
1
5
Order By: Relevance
“…In light of these outcomes and their ensuing differences, we agree with Deng et al (2021) that additional studies with aMMP-8…”
supporting
confidence: 81%
See 3 more Smart Citations
“…In light of these outcomes and their ensuing differences, we agree with Deng et al (2021) that additional studies with aMMP-8…”
supporting
confidence: 81%
“…In the exclusion criteria, Deng et al (2021) state that patients who had received supportive periodontal treatment (supragingival cleaning) were not excluded from their study. That may have improved the oral health of patients in both healthy/gingivitis and periodontitis groups, which consequently might have affected the aMMP-8 POCT results by Deng et al (2021). Additionally, Sorsa, Alassiri, et al (2020) used aMMP-8 POCT with 20 ng/ml in their study, whereas Deng et al (2021) used 10 ng/ml as the cut-off.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Since a large portion of our population had aMMP-8 values below 10 ng/ml (undetectable levels), we performed and reported analyses with different cut-off values (Deng et al, 2021a). Data showed that raising the cut-off value for a positive test from 10 to 20 ng/ml resulted in a decrease in sensitivity (from 33.2% to 17.5%).…”
mentioning
confidence: 99%